A hybrid algorithm for solving inverse problems in elasticity - Barabasz, Barbara; Gajda-Zagórska, Ewa; Migórski, Stanisław; Paszyński, Maciej; Schaefer, Robert; Smołka, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
The paper offers a new approach to handling difficult parametric inverse problems in elasticity and thermo-elasticity, formulated as global optimization ones. The proposed strategy is composed of two phases. In the first, global phase, the stochastic hp-HGS algorithm recognizes the basins of attraction of various objective minima. In the second phase, the local objective minimizers are closer approached by steepest descent processes executed singly in each basin of attraction.
Keywords: inverse problem; hierarchic genetic strategy; hybrid optimization; automatic hp-adaptive finite element method